Physical Therapists’ Use of Psychological Skills Training in Rehabilitation Following Traumatic Knee Injury: An Online Survey Study - Niklas Cederström; Jonas Bloch Thorlund; Britt Elin Øiestad; Kristoffer Henriksen; Eva Ageberg (International Journal of Sports Physical Therapy)
# Background